A Study Of The Economies Of Poland And Romania During Communism Period (1945- 1989) - Ivanov, Laurentiu (European Scientific Journal, ESJ, 2016)
The present economic crisis has highlighted a country in transition to a market economy, which has not experienced economic recession: Poland. The Polish experience cannot be overlooked because the country‘s positive economic evolution was completely different from the evolution of the largest European economies, many of them facing distressful situations for long periods of time. The question to be addressed in this paper is „Could the present economic realities be partially influenced by the historical evolution of a country?“ In an attempt to provide an answer to this question, the present paper will highlight the social and economic developments in Romania and Poland in relation to developed countries for the period 1945-1989 and will conduct a comparative analysis between the two countries. The conclusions of the present study will be the starting point in a comparative analysis of the two countries in the post-communist period.